Influence of γ-ray modified MWCNTs on the structural and thermal properties of high-density polyethylene. (August 2016) - Ghafoor, Bilal; Mehmood, Malik Sajjad; Shahid, Umair; Baluch, Mansoor A.; Yasin, Tariq
Abstract: This study aims to investigate the influence of adding 100 kGy γ-irradiated multi wall carbon nano tubes (MWCNTs) on the structural and thermal properties of high-density polyethylene (HDPE). The effects of further γ-irradiation in the presence of γ-MWCNTs on aforementioned properties have also been investigated. FTIR spectroscopic measurements of HDPE and HDPE/γ-MWCNTs composites reveal that modification of MWCNTs with ≤100 kGy of γ-dose reduces its efficiency as free radical quencher. This behavior is found to increase further with the increase in the concentration of γ-MWCNTs. Wide angle X-ray diffraction (WAXD) data shows a decrease in percent crystallinity and shifting of crystalline peaks toward lower values of 2θ angles. This behavior is mainly attributed to the oxidation induced due to residual free radicals. Thermal analysis reveals that addition of γ-MWCNTs decreases the thermal stability as far as onset thermal degradation temperature, percent crystallinity, and melting temperature of UHMWPE/γ-MWCNTs. In addition to this, gel content measurements show that insoluble percentage of UHMWPE is higher with the incorporation γ-MWCNTs and further irradiation. The gel contents are found to improve up to 29% and 60%, respectively with the incorporation of γ-MWCNTs and further irradiation. Highlights: Nano composites of HDPE with 100-kGy irradiated MWCNTs are made. The effect of incorporation of γ-ray modified MWCNTs in HDPE is studied. Structural and thermal stability of HDPE/γ-MWCNTs nano composites is studied.